ENTREPRENEURSHIP ANTECEDENT ON STUDENT (CASE : FEMALE STUDENTS FINAL YEAR ON GUNADARMA UNIVERSITY) - Marliza Ganefi; Sri Wulan Windu Ratih; Ati Harmoni (Jurnal Ilmiah Ekonomi Bisnis, 2012)
The purpose of this study is to examine and identify antecedents of female student entrepreneurial intention. This research attempts to investigate whether self-efficacy, perceptions of opportunities, prior knowledge of other entrepreneurs, and fear of failure are predictors of female student intention to be entrepreneur. As much as 233 students in their final year, selected proportionally from 12 study programs in Gunadarma University participated in the survey. Data was collected using questionnaire. The results suggest that self-efficacy and perceptions of opportunities were antecedent for entrepreneur intention, while prior knowledge of other entrepreneurs and the fear of failure were not a determining factor for female student entrepreneurial intention.Key Words : antecedent, self-efficacy, entrepreneur intention, female student